Violence against women from the perspective of Primary Care users (Research, Society and Development, 2021)
This study aims to identify the perception of people using primary care about violence against women. This is a qualitative, descriptive and exploratory study, with 18 health service users from nine basic family health units in the municipality of Rio Grande as participants. Data collection took place between October 2019 and January 2020 through a recorded interview with a semi-structured questionnaire, in addition to asking participants to list words that would naturally come to mind when hearing the theme of violence against women. These words were analyzed by the free online program Wordcloud®. The treatment of the interviews was done through Content Analysis. Approval was obtained from the Ethics Committee. From this analysis, three categories emerged: “Gender and violence: recognition of inequalities”; “Feelings and (in) understanding in the face of violence” and “Support for the victim of violence: protection services”. The participants found it difficult to conceptualize the word gender, associating the term directly to people's sexuality. Still, they pointed out to recognize the existence of the Maria da Penha law, however they highlighted the fragility of the protection services pointed out as prejudiced and discriminatory environments. It is necessary to encourage the population to change habits and attitudes, considering that violent behavior follows a pre-established pattern linked to a sexist and sexist culture.